Laban's evil eye : a cognitive linguistic interpretation of ʾl yḥr vʿyny ʾdny in Gen 31:35 - Kotze, Z. (Old Testament essays, 2006)
Rachel's words in Genesis 31:35, ʾl yḥr vʿyny ʾdny, is commonly interpreted as a plea to her father not to get angry. Making use of the cognitive theory of metaphor, this article evaluates the validity of such an interpretation. It is demonstrated that this linguistic expression constitutes a creative metaphor of which the motivation cannot be limited to bodily symptoms of anger, as is commonly assumed. The ancient Near Eastern belief in the evil eye provides an ideal cognitive framework for the interpretation of this expression. It is concluded that a double entendre was probably intended which hinted at both Laban's potential anger as well as his jealousy.